Exploring half root-stress approach: current knowledge and future prospects. (2nd January 2020) - Iqbal, Nasir; Hussain, Sajad; Raza, Muhammad Ali; Safdar, Muhammad Ehsan; Hayyat, Muhammad Sikander; Shafiq, Iram; Yang, Wen-Yu; Liu, Jiang
ABSTRACT: A half-root stress is a half portion of the root system exposed to treatment while the remaining half portion kept under normal conditions. A half-root stress including half-root drought stress, half-root nutrient stress, and half-root salinity stress has become a general approach to improve plant performance and adaptability. Plants produce some chemical signals in stressed part of root, and other parts sense these signals to improve the acclimation and adaptive responses to environmental stresses. Plants adapt the compensatory functions and discriminate the systemic and local regulatory mechanisms, but the understanding of these mechanisms is controversial. Chemical signals (Abscisic acid, sap pH, cytokinins, content of malate, amino acid, and ureide) have been involved in root to shoot signaling under half-root stress. Furthermore, naturally appeared half-root stress in intercropping systems could be an additional attribute of half-root stress approach. Therefore, much more study is required to elaborate its acceptability in intercropping. In this review, we summarized the current knowledge and identified some key future researches areas regarding half-root stress approach.